Urogenital surgery in foals - Saitua, A.; Sanchez de Medina, A.; Bulnes, F.; Buzon, A.; Miraz, R.; Argüelles, D.; Diez de Castro, E. (Frontiers in Veterinary Science, 2025)
Urogenital surgery in foals represents a nuanced and intricate aspect of equine veterinary medicine. Disorders affecting the urinary system in newborn foals can occur at varying rates, with conditions like uroperitoneum and patent urachus being prevalent. Bladder surgeries are typically conducted through laparotomy, while laparoscopic interventions are less common. Procedures to address umbilical remnants encompass surgeries for persistent urachus or omphalitis. Rarer conditions like ectopic ureters or hydroureters may necessitate sophisticated diagnostic and therapeutic measures, including advanced imaging and minimally invasive surgical techniques, despite limited available literature on them. Post-operative complications from urogenital surgeries often involve issues associated with abdominal procedures and potential bladder closure site dehiscence, along with systemic challenges like significant electrolyte imbalances or the risk of sepsis, particularly in cases where foals have not received appropriate passive immunity transfer or pre-operative medical management. This review addresses the prevalent disorders impacting the urogenital system of neonatal foals, emphasizing their surgical treatment, potential risks, and anticipated results. The complexity of neonatal urogenital conditions requires a meticulous approach to the diagnostic work-up and therapeutic plan. Surgical approaches can range from routine to complex, requiring expert knowledge of anatomy and advanced surgical training. Complications occur and the clinician must be prepared to navigate these complications to ensure patients survival.